Pengaruh Kesadaran, Citra, dan Loyalitas Merek Terhadap Keputusan Pembelian Produk Skintifik di Kecamatan Bungku Tengah Kabupaten Morowali - Besse Ariska; Sri Wanti; Syamsul Bachri; Moh. Zeylo Auriza (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The purpose of this study is to analyze the effects of merek loyalty, citra, and kesadaran on the purchase of Skintific products in Kecamatan Bungku Tengah, Kabupaten Morowali. Research is conducted using a quantitative approach using deskriptif and kausal methods. The study's population comprises consumers who use Skintific products in that region, with a sample of about 100 respondents chosen using the purposive sampling technique. The study's findings indicate that: 1) Merek loyalty, citra, and kesadaran together have a significant impact on purchasing decisions. 2) Generally speaking, kesadaran merek has a positive and significant impact on purchasing decisions. 3) Citra merek also has a positive and statistically significant impact. 4) On the other hand, loyalty in a parsial manner does not indicate a significant impact on the purchase of Skintific products in Kecamatan Bungku Tengah, Kabupaten Morowali.